What factors affect income inequality and economic growth in middle-income countries? - Duc Hong Vo; Thang Cong Nguyen; Ngoc Phu Tran; Anh The Vo (Journal of Risk and Financial Management, 2019)
Income inequality in many middle-income countries has increased at an alarming level. While the time series relationship between income inequality and economic growth has been extensively investigated, the causal and dynamic link between them, particularly for the middle-income countries, has been largely ignored in the current literature. This study was conducted to fill in this gap on two different samples for the period from 1960 to 2014: (i) a full sample of 158 countries; and (ii) a sample of 86 middle-income countries. The Granger causality test and a system generalized method of moments (GMM) are utilized in this study. The findings from this study indicate that causality is found from economic growth to income inequality and vice versa in both samples of countries. In addition, this study also finds that income inequality contributes negatively to the economic growth in the middle-income countries in the research period.
Keywords: O15; O47; 330; income inequality; economic growth; middle income countries; Granger causality test; system GMM